Law and literature: Regarding Enrique López Albújar and César Vallejo - Távara Córdova, Francisco (2022)
Law and literature is a line of research that seeks to create a fruitful dialogue between the set of principles and norms of justice and order of social legal science, and the symbolisation and representation of human and social problems in literature. There are different ways of approaching these disciplinary knowledges. This article explains this interaction based on the experience with justice of the writers Enrique López Albújar (1872-1966) and César Vallejo (1892-1938). It is proposed that the interaction between law and literature should be carried out on three levels: approaching the intellectual formation of the authors, focusing on their experience with justice and analysing how the theme of justice is represented in their texts.